Pengaplikasian Tingkatan Sistem Manajemen Mutu pada Proyek Konstruksi (Quality Onspection, Quality Control, Quality Assurance, dan Total Quality Management) - Fanny Chynthia Ferdiana; Jati Utomo Dwi Hatmoko; Bagus Hario Setiadji (Syntax Corporation, 2023)
A competitive strategy that can be relied upon by construction service providers and consultant services is a quality strategy.. A construction has five overall construction project aspects, that is the cost aspect, the time aspect, the quality aspect, the environmental aspect and the K3 aspect. In the context of construction there are several parts that become the level of quality management, that is Quality Inspection, Quality Control, Quality Assurance, and Total Quality Management. The method used to determine the process of implementing quality management in X construction projects is a qualitative method by reviewing, analyzing project contract documents based on quality aspects and some literature. The results of this study are that each level of quality management in this project is able to apply quality management well by taking into account all the conditions of use and the provisions that apply and have been agreed upon. In X construction projects implement quality planning using the reference SNI and ASTM (American Standard and Testing Material).